Konflik Masyarakat Adat pada Pembangunan Ibu Kota Negara dalam Perspektif Sosiologi Hukum - Aulia, Dhine Putri; Ramdani, Nisa Fitri; Alfiyah, Yasmin; Harahap, Chisa Belinda (UIN Sunan Gunung Djati Bandung, 2025)
Law is a rule that contains orders for the creation of safe, orderly conditions and there are sanctions for those who violate it. Law has a role in creating justice in the context of various problems. Law also functions as a means of enforcing justice when violations or social conflicts occur. However, conflicts that occurred in Kutai Kartanegara Regency and Penajam Paser Utara Regency, conflicts that occurred between indigenous peoples and the government as a result of the development of IKN. The purpose of this study is to analyze the conflicts that occurred in North Penajam Paser and Kutai Kartanegara as a result of the development of IKN which caused the eviction of local indigenous peoples that occurred in the balik tribe and the paser tribe, using qualitative research with a literature study approach with an analysis of Roscoe Pound's theory that sees law as a tool of social engineering. Analysis of the conflicts that occurred between the community and the government with the development of IKN in East Kalimantan shows that the law has not been able to fulfill the principles of social justice and inclusiveness as expressed in the theory of law as a tool of social engineering.